Certain aspects of church-state dynamics: legal naming issues within Ukrainian Orthodoxy in the context of the Russian‑Ukrainian war - Yanauer, Mechyslav (War in Ukraine, 2025)
In the context of the Russian-Ukrainian war, the relationship between church and state in Ukraine has gained heightened significance. Ukraine’s efforts to establish a policy that respects religious freedom have been challenged by the invasion, with President Putin leveraging church-state dynamics to support his actions. This article investigates the legal and administrative complexities surrounding the Ukrainian Orthodox Church and its ties to the Moscow Patriarchate. It highlights the necessity for Ukraine to adhere to European democratic and human rights standards while addressing the critical issue of national security, emphasizing the need for a thoughtful and lawful resolution to these ongoing challenges.